Republic of Moldova : Technical Assistance Report-Financial Sector Stability Review. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The mission conducted a diagnostic review of the financial system and proposes a Technical Assistance Roadmap (TARM) to support the authorities' efforts to strengthen their detection of risks and vulnerabilities and to enhance capacity in financial sector oversight and development. Two modules were undertaken during this FSSR mission. The financial stability module focused on areas agreed with the NBM and NCFM during the scoping stage: financial sector oversight, financial stability (macroprudential framework, systemic risk assessment, and stress testing), financial crisis management, financial inclusion and capital markets development. The financial sector statistics module focused on key data gaps hampering financial stability analysis as well as statistical reporting to the IMF's Statistics Department.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy